Magnetic resonance imaging of the elbow in athletes - Stevens, K. J.; McNally, E. G. (Clinics in Sports Medicine, 2010)
Acute and chronic elbow pain is common, particularly in athletes. Although plain radiographs, ultrasound, and computed tomography all have a role to play in the investigation of elbow pain, magnetic resonance imaging (MRI) has emerged as the imaging modality of choice for diagnosis of soft tissue disease and osteochondral injury around the elbow. The high spatial resolution, excellent soft-tissue contrast, and multiplanar imaging capabilities of MRI make it ideal for evaluating the complex joint anatomy of the elbow. This article reviews imaging of common disease conditions occurring around the elbow in athletes, with an emphasis on MRI.